Tyrosine phosphatase Shp2 accelerated the progression of dilated cardiomyopathy via upregulating NF-κB/Src/FAK signaling induced ROS and mitophagy - Hao, Jingxia; Wang, Hua; Li, Bo; Chen, Jingshi; Wang, Wenlu; Wang, Yingxue; Zhang, Yingqian (Scientific reports, 2025)
The purpose of this study was to investigate whether tyrosine phosphatase Shp2 can promote the progression of dilated cardiomyopathy by upregulating intracellular oxidative stress and subsequently promoting mitophagy. Macrophage-specific Shp2 knockout mice were cultured and a dilated cardiomyopathy model was established. Ultrasonography, Masson staining and WGA staining were used to detect the condition of mouse hearts. Immunofluorescence, Western blot and EL were used to detect the expression of relevant proteins in mouse myocardial tissues. Transmission electron microscopy was used to examine the morphology of mouse myocardial cells and their internal mitochondria. Primary BMMs from wild-type mice and specific Shp2 knockout mice were co-cultured with normal myocardial cell. Western blot was used to detect the expression of relevant proteins in BMMs and myocardial cells. Transwell assay was used to measure the migration and invasion ability of BMMs, and immunofluorescence staining was used to detect the expression level of PINK protein in myocardial cells to validate the Western blot results. Dilated cardiomyopathy was ameliorated in DCM mice with specific knockout of Shp2, which showed attenuation of heart structure, degree of fibrosis in myocardial tissue, and degree of cardiomyocyte dilatation. And the degree of autophagy in myocardial tissue was significantly reduced as observed by western blot and transmission electron microscopy. Subsequent cellular experiments also verified that specific knockdown of Shp2 inhibited the invasion of BMMs. And it also mediated the ROS/NF-κB/Src/FAK signalling pathway to inhibit the expression of related autophagy and apoptosis proteins. Tyrosine phosphatase Shp2 accelerated the progression of dilated cardiomyopathy via upregulating NF-κB/Src/FAK signaling induced ROS and mitophagy.